Coating composition, coating film, substrate with coating film, and method for producing same
A coating composition with epoxy resin, silicone resin, aluminum, and an amine curing agent addresses the challenges of incomplete curing and adhesion issues, providing a heat-resistant and corrosion-resistant coating film for high-temperature applications.
Patent Information
- Application Number
- JP2022544574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-08-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-08-23
AI Technical Summary
Existing coating compositions for high-temperature applications, such as steam pipes on ships, face challenges with incomplete curing at room temperature, poor heat resistance, and interlayer adhesion due to incompatibility between epoxy and silicone resins, leading to corrosion and deterioration of physical properties.
A coating composition comprising epoxy resin, silicone resin, aluminum, and an amine curing agent, optionally with a silane coupling agent, which allows for curing at room temperature and enhances heat resistance, corrosion resistance, and interlayer adhesion.
The composition forms a coating film with excellent heat resistance, corrosion resistance, and interlayer adhesion, even at room temperature, effectively protecting substrates exposed to high temperatures and preventing deterioration of physical properties.
Smart Images

Figure 0007605845000007 
Figure 0007605845000001 
Figure 0007605845000002
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to a coating composition, a coating, a coated substrate, or a method for producing the same. [Background technology]
[0002] Among the substrates that require corrosion resistance, there are those that may be exposed to high temperatures (e.g., 200° C.) Examples of such substrates include steam pipes in ships, the temperature of which may rise to approximately 200° C. For substrates that may be exposed to such high temperatures, epoxy resin-based coating compositions, which have excellent corrosion resistance but a heat resistance temperature of about 150°C, cannot be used, and so far only silicone resin-based coating compositions, which have excellent heat resistance, such as the heat-resistant coating composition described in Patent Document 1, have been used. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-6982 A Summary of the Invention [Problem to be solved by the invention]
[0004] It is often difficult to heat-dry (bake) the paint composition applied to substrates such as the steam pipes of ships, and so typically, no heating is performed when forming the coating, but the coating is formed at room temperature and then hardened as the temperature rises during use of the substrate. However, since silicone resin-based heat-resistant paint compositions such as those described above generally require a temperature of 250°C or higher to completely harden, the composition applied to substrates such as steam pipes of ships, which only rise to a temperature of around 200°C, does not completely harden. As a result, it has been found that there is room for improvement in terms of corrosion resistance of the coating film that is formed.
[0005] Furthermore, in order to produce a coating film with excellent long-term corrosion resistance, the dry film thickness must be 100 μm or more. However, it is not easy to form such a thick coating film in a single coat. Therefore, the coating composition is usually applied and dried as a single coating film formation process, and this coating film formation process is repeated multiple times (preferably twice) (hereinafter also referred to as "multiple coats") to form a thick coating film.
[0006] In order to improve the corrosion resistance of the coating film formed from the silicone resin-based heat-resistant coating composition, it is possible to add an organic component having excellent corrosion resistance. However, since organic components generally have poor heat resistance, it is easy to imagine that when exposed to the high temperatures, carbonization or the like occurs, and the coating film properties deteriorate, and the state and color of the coating film cannot be prevented from changing. Furthermore, when organic components are blended in this manner, since silicone resin is an inorganic resin, it has extremely poor compatibility when combined with organic components, and it has been found that problems arise with the adhesion between the coating films formed when applying multiple coats as described above (hereinafter also referred to as "interlayer adhesion").
[0007] One embodiment of the present invention provides a coating composition that can form a coating film that is excellent in heat resistance, corrosion resistance and interlayer adhesion even when cured at room temperature. [Means for solving the problem]
[0008] As a result of extensive research into methods for solving the above problems, the present inventors have found that the above problems can be solved by the following configuration examples, and have thus completed the present invention. A configuration example of the present invention is as follows.
[0009] <1> A coating composition comprising an epoxy resin (A), a silicone resin (B), aluminum (C), and an amine-based curing agent (D).
[0010] <2> Further, a silane coupling agent is included. <1> The coating composition according to claim 1.
[0011] <3> A heat-resistant paint composition, <1> or <2> The coating composition according to claim 1.
[0012] <4> <1> ~ <3> A coating film formed from the coating composition according to any one of claims 1 to 5. <5> Substrate and <4> and a coating film according to any one of claims 1 to 4.
[0013] <6> A method for producing a substrate with a coating film, comprising the following steps [1] and [2]: [1] The base material is <1> ~ <3> A step of applying the coating composition according to any one of the above. [2] A step of drying the coating composition applied to the substrate to form a coating film. Effect of the Invention
[0014] According to one embodiment of the present invention, a coating film having excellent heat resistance, corrosion resistance, and interlayer adhesion can be formed by curing at room temperature. In particular, according to one embodiment of the present invention, even for substrates requiring corrosion resistance that may be exposed to high temperatures (e.g., 200°C), such as steam pipes in ships, a coating film having excellent heat resistance, corrosion resistance, and adhesion to substrates, which can suppress deterioration of coating film properties and changes in coating film state and color, can be formed by curing at room temperature. According to one embodiment of the present invention, even if a thick coating film is formed by applying multiple coats, the adhesion between the coating films formed is excellent, so that a coating film with excellent long-term corrosion prevention properties can be easily formed. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic diagram of a cut test plate used in the corrosion prevention test of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] ≪Paint composition≫ A coating composition according to one embodiment of the present invention (hereinafter also simply referred to as "the composition") contains an epoxy resin (A), a silicone resin (B), aluminum (C), and an amine-based curing agent (D). When epoxy resin (A) and silicone resin (B), which are usually incompatible, are included, peeling is likely to occur between the coating layers formed by multiple coatings, but this composition, although it contains epoxy resin (A) and silicone resin (B), can form a coating film with excellent interlayer adhesion by including aluminum (C). Furthermore, although it contains epoxy resin (A), it can form a coating film that is unlikely to deteriorate in the coating film properties or change in the coating film state or color even when exposed to high temperatures (e.g., 200°C). For this reason, the composition is suitable for use in substrates that require corrosion resistance and can be exposed to high temperatures (e.g., 200°C), and specifically, is suitable for use in steam pipes on ships, piping used in oil refineries and chemical plants, industrial piping (e.g., industrial piping covered with thermal insulation material, etc.), etc. Furthermore, the present composition can be suitably used as a heat-resistant coating composition and / or an anticorrosive coating composition, and can be more suitably used as a heat-resistant and anticorrosive coating composition.
[0017] The composition may be a one-component composition, but is usually a two-component composition consisting of a base component containing an epoxy compound (A) and a curing agent component containing an amine-based curing agent (D). If necessary, the composition may be a three-component or more composition. The base component and the hardener component are usually stored, preserved, transported, etc. in separate containers, and are mixed together immediately before use.
[0018] The composition may be diluted with a solvent before use depending on the coating method, etc. The following descriptions, except for those related to dilution, are for the composition before dilution.
[0019] <Epoxy resin (A)> The epoxy resin (A) is not particularly limited, and any conventionally known epoxy resin can be used. Examples of the epoxy resin (A) include the non-tar epoxy resins described in JP-A-11-343454 and JP-A-10-259351. The epoxy resin (A) contained in the present composition may be one type or two or more types.
[0020] Examples of the epoxy resin (A) include polymers and oligomers containing two or more epoxy groups in the molecule, and polymers or oligomers produced by ring-opening reaction of these epoxy groups. Examples of such epoxy resins include glycidyl ether type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, bisphenol type epoxy resins, novolac type epoxy resins, aliphatic epoxy resins, alicyclic epoxy resins, fatty acid modified epoxy resins, and epoxidized oil-based epoxy resins. Among these, bisphenol type epoxy resins are preferred, bisphenol A type and bisphenol F type epoxy resins are more preferred, and bisphenol A type epoxy resins are particularly preferred, from the viewpoint of being able to easily form a coating film having excellent adhesion to the substrate.
[0021] Examples of the epoxy resin (A) include bisphenol A type epoxy resins (bisphenol A type diglycidyl ethers); bisphenol AD type epoxy resins; bisphenol F type epoxy resins; phenol novolac type epoxy resins; cresol novolac type epoxy resins; and trishydroxyphenylmethane type epoxy resins. Hydrogenation reaction products (hereinafter also referred to as "hydrogenation") of these resins, fatty acid modified products, and brominated products in which at least one of the hydrogen atoms in the resin is replaced with a bromine atom may also be used.
[0022] Examples of the bisphenol A type epoxy resin include condensation polymers of bisphenol A type diglycidyl ethers such as bisphenol A diglycidyl ether, bisphenol A (poly)propylene oxide diglycidyl ether, bisphenol A (poly)ethylene oxide diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, hydrogenated bisphenol A (poly)propylene oxide diglycidyl ether, and hydrogenated bisphenol A (poly)ethylene oxide diglycidyl ether.
[0023] The epoxy resin (A) may be obtained by synthesis using a conventional method, or may be a commercially available product. Examples of the commercially available product that is liquid at room temperature (15 to 25°C, the same applies below) include "E-028" (manufactured by Ohtake Meishin Chemical Co., Ltd., bisphenol A type epoxy resin, epoxy equivalent 180 to 190, viscosity 12,000 to 15,000 mPa·s / 25°C), "jER-807" (manufactured by Mitsubishi Chemical Co., Ltd., bisphenol F type epoxy resin, epoxy equivalent 160 to 175, viscosity 3,000 to 4,500 mPa·s / 25°C), and "FLEP 60" (manufactured by Toray Fine Chemicals Co., Ltd., epoxy equivalent about 280, viscosity about 17,000 mPa·s / 25°C). Examples of the epoxy resin that is semi-solid at room temperature include "jER-834" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 230 to 270). Examples of the epoxy resin that is solid at room temperature include "jER-1001" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 450 to 500), "JER-1004" (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 875 to 975, viscosity Q to U Gardner Holdt / 25°C), and "1007" (manufactured by KUKDO CHEMICAL, bisphenol A type epoxy resin, epoxy equivalent 1,750 to 2,200, viscosity Y to Z1 Gardner Holdt / 25°C). In addition, the aforementioned semi-solid or solid epoxy resin may be diluted with a solvent to form a solution, such as "E-834-85X" (manufactured by Ohtake Meishin Chemical Co., Ltd., a xylene solution of bisphenol A type epoxy resin (834 type epoxy resin solution), epoxy equivalent approximately 300) or "E-001-75" (manufactured by Ohtake Meishin Chemical Co., Ltd., a xylene solution of bisphenol A type epoxy resin (1001 type epoxy resin solution), epoxy equivalent approximately 630). In this specification, the epoxy equivalent refers to the epoxy equivalent of the solid content of the epoxy resin (A).
[0024] The epoxy equivalent of the epoxy resin (A) is preferably 150 or more, more preferably 175 or more, and particularly preferably 200 or more, from the viewpoint of being able to easily form a coating film having excellent corrosion resistance, and is preferably 5,000 or less, more preferably 3,000 or less, and particularly preferably 2,500 or less.
[0025] The weight average molecular weight of the solid content of the epoxy resin (A) measured by GPC (gel permeation chromatography) is not necessarily determined depending on the coating and curing conditions of the resulting composition (e.g., room temperature drying or heat drying), but is preferably 350 to 20,000.
[0026] The solid content of the epoxy resin (A) is preferably 1 mass % or more, more preferably 5 mass % or more, and is preferably 60 mass % or less, more preferably 50 mass % or less, relative to 100 mass % of the nonvolatile content of the composition, from the viewpoint of being able to form a coating film with more excellent corrosion resistance, etc. When the composition is a two-component composition consisting of a main component and a curing agent component, the epoxy resin (A) is contained in the main component. The content of the solid content of the epoxy resin (A) relative to 100% by mass of the solid content of the main component is preferably 1% by mass or more, more preferably 5% by mass or more, and preferably 60% by mass or less, more preferably 50% by mass or less.
[0027] <Silicone resin (B)> The silicone resin (B) is a resin having a siloxane bond, and is not particularly limited as long as it does not contain an epoxy group, and may be linear or branched. The silicone resin (B) is also a siloxane-based binder or a siloxane-based bonding agent. The silicone resin (B) contained in the present composition may be one type, or two or more types.
[0028] Examples of the silicone resin (B) include compounds that have reactive groups in the molecule via siloxane bonds, and that react with each other to form a high molecular weight or a three-dimensional crosslinked structure and harden. Examples of the reaction include condensation reactions and addition reactions. Condensation reactions include dehydration reactions and dealcoholization reactions.
[0029] The silicone resin (B) is preferably, for example, a compound represented by the following formula (I).
[0030] [ka] [In formula (I), R 1 each independently represents an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 8 carbon atoms, or an alkoxy group having 1 to 8 carbon atoms; R 2 each independently represents an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 8 carbon atoms, or a hydrogen atom, and n represents the number of repetitions.]
[0031] R 1 and R 2 Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, and a pentyl group. R 1 and R 2 The aryl group having 6 to 8 carbon atoms may be a group having a substituent such as an alkyl group on the aromatic ring, and examples thereof include a phenyl group, a methylphenyl group, and a dimethylphenyl group. R 1 Examples of the alkoxy group having 1 to 8 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, and a phenoxy group.
[0032] R 1 is preferably a methyl group, an ethyl group, a propyl group or a phenyl group, R 2 is preferably a methyl group, an ethyl group, a phenyl group or a hydrogen atom.
[0033] The silicone resin (B) is preferably a heat-resistant resin such as a methylsilicone resin or a methylphenylsilicone resin, and more preferably contains one or more structural units selected from the group consisting of the following dimethylsiloxane unit (b1), diphenylsiloxane unit (b2), monomethylsiloxane unit (b3), monopropylsiloxane unit (b4) and monophenylsiloxane unit (b5).
[0034] [ka] [In formulae (b1) to (b5), in Si-O-, "-" that is bonded to O and not bonded to Si represents a bond, and Si-O- does not necessarily represent Si-O-CH3.]
[0035] The weight average molecular weight (hereinafter also simply referred to as "Mw") of the silicone resin (B) in terms of standard polystyrene, as measured by GPC (gel permeation chromatography), is preferably 15,000 or more, more preferably 18,000 or more, and is preferably 1,000,000 or less, more preferably 600,000 or less, from the viewpoint of being able to easily form a coating film having excellent heat resistance and corrosion resistance, etc. The number of repetitions n is preferably selected so that the Mw of the silicone resin (B) is in the above range.
[0036] The solids content of the silicone resin (B) is preferably 1 mass % or more, more preferably 3 mass % or more, and is preferably 60 mass % or less, more preferably 50 mass % or less, relative to 100 mass % of the nonvolatile content of the composition, from the viewpoint of being able to easily form a coating film that has an excellent balance between corrosion resistance, heat resistance, and interlayer adhesion. When the composition is a two-component composition consisting of a main component and a curing agent component, the silicone resin (B) may be contained in either the main component or the curing agent component.
[0037] The ratio of the solid content of the epoxy resin (A) to the solid content of the silicone resin (B) in the composition ((A):(B)) is preferably 1:20 to 50:1, more preferably 1:10 to 10:1, and particularly preferably 1:5 to 5:1, from the viewpoint of being able to easily form a coating film having an excellent balance of heat resistance, corrosion resistance, and interlayer adhesion.
[0038] <Aluminum (C)> The aluminum (C) is not particularly limited, but is preferably in a powder form, and may be a flaky aluminum powder or a non-flaky aluminum powder other than a flake. As a raw material for preparing the present composition, aluminum in not only powder form but also paste form may be used. The aluminum powder (B) contained in the present composition may be of one type or of two or more types.
[0039] The term "scaly" refers to a shape that is shaped like a scale, and although there is no particular range that is specified, typically, the aspect ratio is preferably 5 or more, more preferably 10 or more, and even more preferably 20 or more, and is preferably 150 or less, and more preferably 120 or less. In addition, the term "non-scaly" refers to a shape other than a scale shape, such as a spherical shape, teardrop shape, or spindle shape, and although there is no particular range that is specified, the aspect ratio is usually preferably less than 5, more preferably 1 or more, and more preferably 3 or less.
[0040] The aspect ratio can be measured using an electron microscope by observing the aluminum powder using a scanning electron microscope (SEM), such as "XL-30" (trade name; manufactured by Philips Corporation), measuring the thickness and maximum length on the main surface (or the length of the major axis and the length of the minor axis) of several tens to several hundreds of powder particles, and calculating the average value of these ratios (maximum length on the main surface / thickness, or the length of the major axis / the length of the minor axis). The thickness of the aluminum powder can be measured by observing the powder from a horizontal direction relative to the main surface (the surface with the largest area), and the maximum length of the main surface of the aluminum powder means, for example, the length of the diagonal if the main surface is rectangular, the diameter if the main surface is circular, and the length of the major axis if the main surface is elliptical. The length of the major axis of the aluminum powder is specifically the longest length in a cross-sectional view near the center of the powder, and the length of the minor axis of the aluminum powder is the length of a line perpendicular to the major axis at the center of the cross-sectional view.
[0041] From the viewpoint of easily forming a coating film with superior corrosion resistance, the median diameter (D50) of the scaly aluminum powder is preferably 100 μm or less, more preferably 5 μm or more, more preferably 70 μm or less, and particularly preferably 50 μm or less. From the viewpoint of easily obtaining a composition with a low VOC content and excellent coating workability, the median diameter (D50) of the non-scaly aluminum powder (D) is preferably 50 μm or less, more preferably 5 μm or more, more preferably 30 μm or less, and particularly preferably 15 μm or less. The D50 is an average value of measurements taken three times using a laser scattering diffraction type particle size distribution measuring device, for example, "SALD 2200" (manufactured by Shimadzu Corporation).
[0042] The scaly aluminum powder may be of the leafing type or the non-leafing type, but it is preferable to use the leafing type in terms of being able to suppress deterioration of the coating film and a decrease in adhesion to the substrate, etc. Furthermore, when the scaly aluminum powder is used, the leafing type and the non-leafing type may be used in combination. The non-flake aluminum powder is preferably aluminum powder produced by an atomization method (spray method).
[0043] The content of aluminum powder (C) in the present composition is preferably 0.1 mass % or more, more preferably 1 mass % or more, and is preferably 30 mass % or less, more preferably 20 mass % or less, relative to 100 mass % of the nonvolatile content of the present composition, from the viewpoints of being able to easily form a coating film that has an excellent balance between corrosion resistance, heat resistance and interlayer adhesion, and being able to easily form a coating film that is more suppressed in terms of deterioration of the coating film properties and changes in the coating film state and hue even when exposed to high temperatures. The content of the aluminum powder (C) in the present composition is, in terms of the same effects as those described above, preferably 1 part by mass or more, more preferably 3 parts by mass or more, and preferably 200 parts by mass or less, more preferably 100 parts by mass or less, per 100 parts by mass of the solid content of the epoxy resin (A). The content of the aluminum powder (C) in the present composition is, in terms of the same effects as those described above, preferably 1 part by mass or more, more preferably 3 parts by mass or more, and preferably 200 parts by mass or less, more preferably 100 parts by mass or less, per 100 parts by mass of the solid content of the silicone resin (B). In view of the same effects as described above, the content of the aluminum powder (C) in the present composition is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and is preferably 100 parts by mass or less, more preferably 50 parts by mass or less, per 100 parts by mass of the total solid content of the epoxy resin (A) and the silicone resin (B).
[0044] <Amine-based hardener (D)> The amine-based curing agent (D) is not particularly limited as long as it is an amine compound, but aliphatic, alicyclic, aromatic, heterocyclic, etc. amine compounds are preferred. These amine compounds are classified according to the type of carbon to which the amino group is bonded. For example, an aliphatic amine curing agent refers to a compound having at least one amino group bonded to an aliphatic carbon. The amine-based curing agent (D) contained in the present composition may be one type, or two or more types.
[0045] Examples of the aliphatic amine curing agent include alkylene polyamines, polyalkylene polyamines, and alkylamino alkyl amines.
[0046] The alkylene polyamine may be, for example, a compound represented by the formula: 1 -NH2" (R 1 is a divalent hydrocarbon group having 1 to 12 carbon atoms. Specific examples thereof include methylenediamine, ethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, and trimethylhexamethylenediamine.
[0047] The polyalkylene polyamine may, for example, be a compound represented by the formula: "H2N-(C m H 2m N.H. n Specific examples of the compound include diethylenetriamine, dipropylenetriamine, triethylenetetramine, tripropylenetetramine, tetraethylenepentamine, tetrapropylenepentamine, pentaethylenehexamine, nonaethylenedecamine, bis(hexamethylene)triamine, and triethylene-bis(trimethylene)hexamine.
[0048] The alkylaminoalkylamine is, for example, a compound represented by the formula: 2 2N-(CH2) p -NH2" (R 2 are independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms (provided that at least one of R 2is an alkyl group having 1 to 8 carbon atoms, and p is an integer of 1 to 6. Specific examples thereof include dimethylaminoethylamine, diethylaminoethylamine, dibutylaminoethylamine, dimethylaminopropylamine, diethylaminopropylamine, dipropylaminopropylamine, dibutylaminopropylamine, and dimethylaminobutylamine.
[0049] Other aliphatic amine curing agents include, for example, tetra(aminomethyl)methane, tetrakis(2-aminoethylaminomethyl)methane, 1,3-bis(2'-aminoethylamino)propane, tris(2-aminoethyl)amine, bis(cyanoethyl)diethylenetriamine, polyoxyalkylenepolyamine (particularly, diethylene glycol bis(3-aminopropyl)ether), bis(aminomethyl)cyclohexane, isophoronediamine (IPDA), menthenediamine (MDA), o-xylylenediamine, m-xylylenediamine (MXDA), p-xylylenediamine, bis(aminomethyl)naphthalene, bis(aminoethyl)naphthalene, 1,4-bis(3-aminopropyl)piperazine, 1-(2'-aminoethylpiperazine), and 1-[2'-(2''-aminoethylamino)ethyl]piperazine.
[0050] Specific examples of the alicyclic amine curing agent include cyclohexanediamine, diaminodicyclohexylmethane (particularly, 4,4'-methylenebiscyclohexylamine), 4,4'-isopropylidenebiscyclohexylamine, norbornanediamine, and 2,4-di(4-aminocyclohexylmethyl)aniline.
[0051] Examples of the aromatic amine curing agent include aromatic polyamine compounds having two or more primary amino groups bonded to an aromatic ring such as a benzene ring or a naphthalene ring. Specific examples of the aromatic amine curing agent include phenylenediamine, naphthalenediamine, diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 4,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenyl sulfone, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, diaminodiethylphenylmethane, 2,4'-diaminobiphenyl, 2,3'-dimethyl-4,4'-diaminobiphenyl, and 3,3'-dimethoxy-4,4'-diaminobiphenyl.
[0052] Specific examples of the heterocyclic amine curing agent include 1,4-diazacycloheptane, 1,11-diazacycloeicosane, and 1,15-diazacyclooctacosane.
[0053] Further examples of the amine-based curing agent (D) include modified amine compounds, for example, fatty acid modified products such as polyamidoamines, amine adducts with epoxy compounds (epoxy adducts of amine compounds), Mannich modified products (e.g., phenalkamine, phenalkamide), Michael adducts, ketimines, and aldimines.
[0054] As the amine-based curing agent (D), polyamidoamine and amine adducts with epoxy compounds are preferred, and amine adducts with epoxy compounds are particularly preferred. By using such an amine curing agent (D), a coating film with excellent corrosion resistance can be easily formed.
[0055] The amine-based curing agent (D) may be obtained by synthesis using a conventionally known method, or may be a commercially available product, such as "TD-961" (manufactured by DIC Corporation), which is a modified aliphatic polyamine (epoxy adduct of ethylenediamine), or "AD-71" (manufactured by Ohtake Meishin Chemical Co., Ltd.), which is a modified aliphatic polyamine (epoxy adduct of diethylenetriamine).
[0056] The active hydrogen equivalent of the amine curing agent (D) is preferably 50 or more, more preferably 100 or more, and is preferably 1,000 or less, more preferably 500 or less, from the viewpoint of being able to easily form a coating film having excellent corrosion resistance. In this specification, the active hydrogen equivalent refers to the active hydrogen equivalent of the solid content of the amine-based curing agent (D).
[0057] From the viewpoint of being able to easily form a coating film that is excellent in corrosion resistance, coating strength and drying properties, etc., it is desirable to use the amine-based curing agent (D) in an amount such that the reaction ratio calculated by the following formula (2) is preferably 0.3 or more, more preferably 0.4 or more, and preferably 1.5 or less, more preferably 1.2 or less.
[0058] Reaction ratio={(amount of solid content of amine-based curing agent (D) / active hydrogen equivalent of amine-based curing agent (D))+(amount of solid content of component reactive to epoxy resin (A) / functional group equivalent of solid content of component reactive to epoxy resin (A))} / {(amount of solid content of epoxy resin (A) / epoxy equivalent of epoxy resin (A))+(amount of solid content of component reactive to amine-based curing agent (D) / functional group equivalent of solid content of component reactive to amine-based curing agent (D))} (2)
[0059] Here, in the formula (2), the "component reactive to the amine curing agent (D)" may, for example, be a component reactive to the amine curing agent (D) in the other components described below, and the "component reactive to the epoxy resin (A)" may, for example, be a component reactive to the epoxy resin (A) in the other components described below. The "functional group equivalent" of each component refers to the mass (g) per 1 mol of functional group obtained by dividing the mass of 1 mol of this component by the number of moles of functional groups contained therein.
[0060] When the composition is a two-component composition consisting of a base component and a curing agent component, the amine-based curing agent (D) is included in the curing agent component. The viscosity of this curing agent component at 25°C measured with an E-type viscometer is preferably 100,000 mPa s or less, more preferably 50 mPa s or more, and more preferably 10,000 mPa s or less, in order to provide a composition with excellent handling properties and coating workability.
[0061] <Other ingredients> The present composition is not particularly limited as long as it contains components (A) to (D), and may contain other components, such as a silane coupling agent, a pigment, a pigment dispersant, an antifoaming agent, an anti-sagging / anti-settling agent (thixotropic agent), a dehydrating agent, a curing accelerator, a curing catalyst, and an organic solvent, if desired, within a range that does not impair the effects of the present invention. These other components may each be used alone or in combination of two or more.
[0062] [Silane coupling agents] By using a silane coupling agent, not only can the adhesion of the resulting coating film to the substrate be further improved, but also the corrosion resistance, such as water resistance and salt water resistance, and heat resistance, of the resulting coating film can be improved. The silane coupling agents may be used alone or in combination of two or more.
[0063] The silane coupling agent is not particularly limited, and a conventionally known compound can be used. However, it is preferable that the silane coupling agent is a compound having at least two functional groups in the same molecule, which can contribute to improving the adhesion to the substrate and reducing the viscosity of the composition. For example, a compound represented by the formula: "X-SiMe n Y 3-n" [wherein n is 0 or 1, X is a reactive group capable of reacting with an organic substance (e.g., an amino group, a vinyl group, an epoxy group, a mercapto group, a halogen group, a group in which a hydrocarbon group is partially substituted with any of these groups, or a group in which a hydrocarbon group is partially substituted with an ether bond or the like and is partially substituted with any of these groups), Me is a methyl group, and Y is a hydrolyzable group (e.g., an alkoxy group such as a methoxy group or an ethoxy group).] is more preferable.
[0064] As the silane coupling agent, an epoxy group-containing silane coupling agent or an amino group-containing silane coupling agent is preferred. The use of an epoxy group-containing silane coupling agent is preferred from the viewpoint of adhesion of the obtained coating film to the substrate and improvement of anticorrosion properties, etc., and the use of an amino group-containing silane coupling agent is preferred from the viewpoint of adhesion of the obtained coating film to the substrate, improvement of anticorrosion properties, improvement of heat resistance, etc. In addition, the use of an amino group-containing silane coupling agent can also suppress discoloration of the obtained coating film.
[0065] Specific examples of commercially available silane coupling agents include "KBM-403" (3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.), "Sila-Ace S-510" (manufactured by JNC Corporation), and "KBM-603" (N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0066] When the present composition contains a silane coupling agent, the content of the silane coupling agent is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and preferably 10 mass% or less, more preferably 5 mass% or less, based on 100 mass% of the non-volatile content of the present composition. When the content of the silane coupling agent is within the above range, the viscosity of the composition can be reduced, and therefore not only the coating workability is improved but also the adhesion to the substrate and the corrosion resistance of the resulting coating film are improved.
[0067] When the present composition contains an epoxy group-containing silane coupling agent, from the viewpoint of the same effect as described above, the content of the epoxy group-containing silane coupling agent is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, relative to 100 mass% of the non-volatile content of the present composition. In addition, when the present composition contains an amino group-containing silane coupling agent, from the viewpoint of the same effect as described above, the content of the amino group-containing silane coupling agent is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, relative to 100 mass% of the non-volatile content of the present composition.
[0068] In addition, when the present composition contains an amino group-containing silane coupling agent, from the viewpoint of the same effect as described above, the content of the amino group-containing silane coupling agent is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the solid content of the silicone resin (B).
[0069] [Pigment] The composition may, and preferably does, contain a pigment. Examples of the pigment include extender pigments, coloring pigments, and rust-preventive pigments, and they may be either organic or inorganic. One type of pigment may be used, or two or more types may be used.
[0070] Examples of the extender pigment include talc, mica, (precipitated) barium sulfate, (potash) feldspar, kaolin, alumina white, bentonite, wollastonite, clay, glass flakes, aluminum flakes, scaly iron oxide, magnesium carbonate, barium carbonate, calcium carbonate, dolomite, and silica. In particular, talc, mica, silica, (precipitated) barium sulfate, and (potash) feldspar are preferred.
[0071] When the present composition contains a body pigment, the content of the body pigment is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, based on 100% by mass of the non-volatile content of the present composition.
[0072] Examples of the color pigment include inorganic pigments such as carbon black, titanium dioxide (titanium white), iron oxide (red oxide), yellow iron oxide, and ultramarine, and organic pigments such as cyanine blue and cyanine green. Titanium white, carbon black, and red oxide are particularly preferred.
[0073] When the present composition contains a coloring pigment, the content of the coloring pigment is preferably 0.1% by mass or more, more preferably 1% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, based on 100% by mass of the non-volatile content of the present composition.
[0074] Examples of the anti-rust pigment include zinc powder, zinc alloy powder, zinc phosphate compounds, calcium phosphate compounds, aluminum phosphate compounds, magnesium phosphate compounds, zinc phosphite compounds, calcium phosphite compounds, aluminum phosphite compounds, strontium phosphite compounds, aluminum tripolyphosphate compounds, molybdate compounds, zinc cyanamide compounds, borate compounds, nitro compounds, and composite oxides.
[0075] When the present composition contains a pigment, the pigment volume concentration (PVC) in the present composition is preferably 10% or more, more preferably 20% or more, and is preferably 60% or less, more preferably 50% or less, from the viewpoints that a composition having excellent coating workability can be easily obtained, and a coating film having excellent adhesion to the substrate due to stress relaxation and excellent corrosion resistance can be easily obtained.
[0076] The PVC refers to the total volume concentration of pigments relative to the volume of non-volatile matter in the composition. The pigments used to calculate the PVC include aluminum (C) and pigments in other components. Specifically, the PVC can be calculated by the following formula: PVC [%] = Total volume of all pigments in the composition × 100 / Volume of non-volatile matter in the composition
[0077] In this specification, the non-volatile content of the composition means the heating residue obtained according to JIS K 5601-1-2 (heating temperature: 125° C., heating time: 60 minutes). The non-volatile content of the composition can also be calculated as the amount excluding the solvent and the organic solvent in the raw materials used. Furthermore, among the components (such as epoxy resin (A)) that are the raw materials constituting the present composition, the base component, or the hardener component, the components other than the solvent in the base component and the hardener component are referred to as "solids".
[0078] The volume of the non-volatile content in the composition can be calculated from the mass and true density of the non-volatile content of the composition. The mass and true density of the non-volatile content may be measured values or values calculated from the raw materials used. The volume of the pigment can be calculated from the mass and true density of the pigment used. The mass and true density of the pigment may be measured values or values calculated from the raw materials used. For example, the volume of the pigment can be calculated by separating the pigment from other components from the non-volatile content of the composition and measuring the mass and true density of the separated pigment.
[0079] [Anti-sagging agents / anti-settling agents (thixotropic agents)] The anti-sagging / anti-settling agent (thixotropic agent) is not particularly limited, but is preferably a material that can suppress the settling of pigments and the like in the present composition and improve its storage stability, or a material that can improve the anti-sagging properties of the present composition during or after coating. As the anti-sagging agent and anti-settling agent, there can be used conventionally known agents such as organoclay waxes such as stearate salts, lecithin salts and alkylsulfonates of Al, Ca and Zn, polyethylene wax, amide wax, hydrogenated castor oil wax, a mixture of hydrogenated castor oil wax and amide wax, synthetic finely powdered silica, and oxidized polyethylene wax. Among these, amide wax, synthetic finely powdered silica, oxidized polyethylene wax and organoclay wax are preferred.
[0080] Such anti-sagging agents and anti-settling agents may be commercially available products, such as "Disparlon 305", "Disparlon 4200-20", and "Disparlon 6650" manufactured by Kusumoto Chemical Industries, Ltd., "ASA T-250F" manufactured by Ito Oil Milling Co., Ltd., "Flonon RCM-300" manufactured by Kyoeisha Chemical Co., Ltd., "Benton SD-2" manufactured by Elementis Specialties, Inc., and the silica-based thixotropic agent "Aerosil R972" (manufactured by Nippon Aerosil Co., Ltd.).
[0081] When the present composition contains an anti-sagging agent / anti-settling agent, the content of the anti-sagging agent (anti-settling agent) is preferably 0.1 to 10% by mass relative to 100% by mass of the non-volatile matter of the present composition.
[0082] [Organic solvents] The organic solvent is not particularly limited, but examples thereof include aromatic hydrocarbon solvents such as toluene and xylene, ketone solvents such as methyl ethyl ketone (MEK) and methyl isobutyl ketone (MIBK), ether solvents such as butyl cellosolve, ester solvents such as butyl acetate, alcohol solvents such as isopropanol, isobutyl alcohol, n-butanol, and propylene glycol monomethyl ether (PGM), and aliphatic hydrocarbon solvents such as mineral spirits, n-hexane, n-octane, 2,2,2-trimethylpentane, isooctane, n-nonane, cyclohexane, and methylcyclohexane.
[0083] When the present composition contains an organic solvent, it is desirable to use the organic solvent in an amount that is preferably 10% by mass or more, more preferably 20% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, based on the content of non-volatile matters in the present composition.
[0084] The VOC (volatile organic component) content of the present composition is preferably 700 g / L or less, more preferably 600 g / L or less, and particularly preferably 500 g / L or less, in order to provide a composition that has little impact on the environment and the human body.
[0085] The VOC content of the composition can be calculated from the following formula (1) using the paint specific gravity and the non-volatile content of the composition. VOC content (g / L) = paint specific gravity × 1000 × (100 - non-volatile content of this composition) / 100 (1)
[0086] Paint specific gravity (g / cm 3 ): The value calculated by filling a 100 ml specific gravity cup with the composition (e.g., the composition immediately after mixing the base component and hardener component) at a temperature of 23°C and measuring the mass of the composition.
[0087] <Coated film and coated substrate> A coating film according to one embodiment of the present invention (hereinafter also referred to as "the present coating film") is formed from the above-mentioned present composition, and a substrate with a coating film according to one embodiment of the present invention is a laminate containing the present coating film and a substrate. A suitable example of the present coating film is a heat-resistant coating film.
[0088] The substrate is not particularly limited, and examples thereof include metal substrates made of steel (iron, steel, ferroalloy, carbon steel, alloy steel, etc.), non-ferrous metals (stainless steel, aluminum, zinc plating, brass, brass, etc.), and metal substrates the surface of which is coated with a shop primer, etc. Examples of the substrate include plant structures, land structures, marine structures, ships, etc., but from the viewpoint of better exerting the effects of the present invention, steam pipes of ships, piping used in oil refineries, chemical plants, etc., and industrial piping (e.g., industrial piping covered with thermal insulation material, etc.), and among these, steam pipes of ships are more preferable.
[0089] The thickness of the coating film is not particularly limited, but is preferably 30 to 400 μm, more preferably 30 to 300 μm, and may be a single layer film formed by one coating or a multi-layer film formed by multiple coatings. In particular, when the substrate is made of steel (iron, steel, ferroalloy, carbon steel, alloy steel, etc.), the thickness of the coating film is preferably 100 μm or more from the viewpoint of long-term corrosion prevention. By using this composition, even when a coating film of such a thickness is formed on a substrate, the coating film is unlikely to blister or crack, and in particular, even when exposed to high temperatures of around 200°C, the coating film is unlikely to blister or crack, making it possible to protect the substrate from corrosion for a long period of time.
[0090] The present coating film is formed from the present composition described above, and specifically, can be produced through a process including the following steps [1] and [2]. [1] A step of applying the composition to a substrate. [2] A step of drying the composition applied to the substrate to form a coating film.
[0091] <Process [1]> The method for applying the composition to a substrate is not particularly limited, and any conventionally known method can be used without limitation, and commonly used methods such as airless spray coating, air spray coating, brush coating, roller coating, etc. are preferred. Spray coating is preferred from the viewpoints of excellent workability and productivity, ease of application to a substrate with a large area, and ability to better exert the effects of the present invention. When the present composition is a two-component composition, it is preferable to mix the main component and the hardener component immediately before application, and then carry out spray application or the like.
[0092] The spray coating conditions may be adjusted as appropriate depending on the thickness of the coating film desired. For example, in the case of airless spraying, the coating conditions may be set as follows: primary (air) pressure: approximately 0.4 to 0.8 MPa, secondary (paint) pressure: approximately 10 to 26 MPa, gun movement speed: approximately 50 to 120 cm / sec. The viscosity of the composition used here is preferably about 1.8 to 2.5 Pa s at 23° C. when measured with a Brookfield viscometer ("TVB-10M", manufactured by Toki Sangyo Co., Ltd.) In order to obtain a composition with such a viscosity, the viscosity of the composition may be adjusted using a thinner or the like. The thinner is preferably an organic solvent capable of dissolving or dispersing the components in the composition, and examples thereof include aromatic hydrocarbon solvents such as toluene and xylene, aliphatic hydrocarbon solvents such as mineral spirits and cyclohexane, and alcohol solvents such as n-butanol and isopropanol. The thinner used may be one type or two or more types.
[0093] When applying the composition to a substrate, it is preferable to treat the substrate surface as necessary (e.g., blast treatment (ISO8501-1 Sa2 1 / 2), degreasing to remove oil and dust) in order to remove rust, oil, moisture, dust, salt, etc. from the substrate and to improve adhesion of the resulting coating film to the substrate. In addition, the substrate may be coated with a shop primer or the like for the purpose of primary rust prevention.
[0094] <Process [2]> The composition can be dried and cured at room temperature, and thus a coating film having excellent heat resistance and corrosion resistance can be obtained even when dried and cured at room temperature. If desired, the composition may be dried under heating to shorten the drying time. The drying conditions are not particularly limited and may be appropriately set depending on the composition, the substrate, the coating location, and the like. The drying temperature is preferably 5 to 40°C, more preferably 10 to 30°C, and the drying time is preferably 18 hours to 14 days, more preferably 24 hours to 7 days.
[0095] As a method for forming a coating film having the desired thickness, a coating film having the desired thickness may be formed by one coating, or a coating film having the desired thickness may be formed by two or more coatings (multiple coatings). From the viewpoint of controlling the thickness of the coating film and taking into consideration the residual solvent in the coating film, it is preferable to form a coating film having the desired thickness by two or more coatings. Note that "two coats" refers to a method in which steps [1] and [2] are performed, and then steps [1] and [2] are performed on the resulting coating film. "Three or more coats" refers to a method in which a series of steps are further repeated.
[0096] When forming a coating by painting two or more times, it is preferable that the hue of the paint / coating applied the first time is different from the hue of the paint / coating applied the next time. This is a measure to make it easier to judge missed coats or insufficient film thickness during the painting work. Also, a top coat may be applied to finish the final exterior surface with a specified hue. EXAMPLES
[0097] The present invention will be further described below with reference to examples, but the present invention is not limited to these.
[0098] [Examples 1 to 16 and Comparative Examples 1 to 10] The materials listed in the columns for the main component in Tables 1 to 3 were mixed in a container in the amounts (parts by mass) listed in each column, and the mixture was stirred at room temperature using a high-speed disperser until uniform, and then further dispersed until the temperature reached 50° C. The mixture was then cooled to 30° C. or lower to prepare the main component of the coating composition. In addition, the materials listed in the hardener component columns of Tables 1 to 3 were mixed in a container in the amounts (parts by mass) listed in each column, and the hardener component was prepared by mixing these components at room temperature and normal pressure using a high-speed disperser. These base components and curing agent components were mixed in the mixing ratios shown in Tables 1 to 3 before coating to prepare coating compositions. The components shown in Tables 1 to 3 are explained in Table 4. The solid content (mass%) of each component in Table 4 is the value in the manufacturer's catalog.
[0099] [Preparation of test panels] Each coating composition prepared as described above was diluted 10% by mass with Epoxy Thinner A (manufactured by Chugoku Toryo Co., Ltd.) (10 g of thinner per 100 g of coating composition). The diluted composition was applied to the surface of a sandblasted steel plate (SS400) with dimensions of 150 mm x 70 mm x 2.3 mm (thickness) (arithmetic mean roughness (Ra): 30 to 75 μm) using a film applicator with a gap of 500 μm so that the dry film thickness was 150 μm (first coat). The coating composition applied to the steel plate was then dried at room temperature (23°C) for 24 hours. Next, the diluted composition was applied (second coat) onto the dried coating (first coating) using a film applicator with a gap of 500 μm so that the dry film thickness was 150 μm, and then dried at room temperature (23° C.) for 3 days to produce a test plate (substrate with coating) in which the first and second coating layers were laminated in that order on a steel plate. The test plates thus prepared were used to carry out the following tests for interlayer adhesion, heat resistance (coating film state after exposure to high temperatures), and heat resistance (resistance to discoloration). The results are shown in Tables 1 to 3.
[0100] <Interlayer adhesion> The interlayer adhesion between the first and second coating layers was evaluated according to the cross-cut method specified in JIS K 5600-5-6:1999. When making the cut, the cut was made from the second coating film side of the test plate to the first coating film side.
[0101] <Heat resistance (coating film condition after exposure to high temperatures)> The test plate prepared as described above was heated at 200° C. for 6 hours and then cooled to room temperature. After cooling to room temperature, the condition of the coating surface was evaluated according to ASTM D714-87. The evaluation is shown by a combination of a number representing the "size of the blister" and a symbol representing the "density of the blister." The "size of the blister" is expressed in order of increasing density with numbers 2, 4, 6, and 8, and 10 being the absence of any blister at all. The "density of the blister" is expressed in order of decreasing density with numbers D, MD, M, and F.
[0102] <Heat resistance (discoloration resistance)> In accordance with JIS K 5600-4-5:1999, the L*, a* and b* of the coating surface on the test plate prepared as described above were measured using a spectrophotometer (Model CM-3700A, manufactured by Konica Minolta Japan, Inc.). The test plate prepared as described above was heated at 200°C for 6 hours and then returned to room temperature, after which the L*, a* and b* of the coating surface on the test plate were measured, and the color difference ΔE of the coating surface before and after exposure to high temperature was calculated in accordance with JIS K 5600-4-6:1999. In addition, the discoloration reduction rates in Tables 2 and 3 are percentages of the ratio of ΔE of the Examples to ΔE of the corresponding Comparative Examples. For example, the discoloration reduction rates of Examples 5 and 6 are percentages of the ratio of ΔE of Examples 5 or 6 to ΔE of Comparative Example 3, and the discoloration reduction rates of Examples 7 and 8 are percentages of the ratio of ΔE of Examples 7 or 8 to ΔE of Comparative Example 4.
[0103] <Glass transition temperature (Tg) measurement> Each coating composition prepared as described above was diluted 10% by mass (10 g of thinner per 100 g of coating composition) with epoxy thinner A (manufactured by Chugoku Paint Co., Ltd.). The diluted composition was applied onto release paper using a film applicator with a gap of 500 μm so that the dry film thickness was 150 μm. The applied coating composition was then dried at room temperature for 7 days, and the coating film removed from the release paper was cut into a circle with a diameter of 3.5 mm. Using the cut-out coating film, the temperature was raised from -50 ° C. at 20 ° C. per minute to 150 ° C. using a DSC Q2000 (manufactured by TA Instruments Japan Inc.). Thereafter, the sample was cooled to -50 ° C., and the temperature was raised from -50 ° C. at 20 ° C. per minute to 150 ° C. in the same manner as above, and Tg was obtained from the DSC curve when the temperature was raised from -50 ° C. at 20 ° C. per minute to 150 ° C. The results are shown in Table 1. It is generally known that the higher the Tg, the better the heat resistance.
[0104] <Mass reduction rate measurement> Each coating composition prepared as described above was diluted 10% by mass (10 g of thinner for 100 g of coating composition) with epoxy thinner A (manufactured by Chugoku Paint Co., Ltd.). The diluted composition was applied onto release paper using a film applicator with a gap of 500 μm so that the dry film thickness was 150 μm. The applied coating composition was then dried at room temperature for 7 days, and the coating film removed from the release paper was cut out to a diameter of 3.5 mm. Using the cut-out coating film, the mass reduction rate of the coating film at 250 ° C. when the temperature was raised from 30 ° C. to 1,000 ° C. at 10 ° C. per minute [(mass of coating film before heating-mass of coating film at 250 ° C.) × 100 / mass of coating film before heating] was measured using STA7300 (manufactured by Hitachi High-Tech Science Co., Ltd.). The results are shown in Table 1. It is generally known that the lower the coating mass loss rate, the more excellent the heat resistance.
[0105] <Corrosion resistance test> [Preparation of test panels] Each coating composition prepared as described above was diluted 10% by mass (10 g of thinner for 100 g of coating composition) using epoxy thinner A (manufactured by Chugoku Paint Co., Ltd.). The diluted composition was applied to the surface of a cold-rolled steel plate (JIS G 3141) of SSPC-SB with dimensions of 150 mm x 70 mm x 0.8 mm (thickness) using an air spray so that the dry film thickness was 100 μm (first coating). Then, the coating composition applied to the steel plate was dried at room temperature (23 ° C.) for 24 hours. Next, the diluted composition was applied to the dried coating film using an air spray so that the dry film thickness was 100 μm (second coating). Then, the plate was dried at room temperature (23 ° C.) for 7 days to prepare each test plate for corrosion resistance evaluation.
[0106] As shown in FIG. 1, cuts 2 were made in each of the obtained test panels 1 for evaluating corrosion resistance at positions 10 mm from both ends of the long sides and 20 mm from either end of the short sides, so that the cuts reached the surface of the base steel plate, with a length of 50 mm. The test plate with the cuts as described above was heated at 200°C for 6 hours, then left to stand at room temperature for 18 hours, and then placed in a salt spray machine (JIS K 5600-7-1 compliant) for 144 hours, which constituted one cycle. After a total of eight such cycles (1,344 hours), if the maximum length from the cut to the part where the coating film peeled off from the steel plate was within 20 mm, it was judged as pass (AA), and if the maximum length exceeded 20 mm, it was judged as fail (DD). The results are shown in Table 1.
[0107] It is believed that the coating films formed from the coating compositions obtained in Examples 1 to 3 and 5 to 16 exhibit anticorrosive properties similar to those of Example 4. Also, as in the comparison between Example 4 and Comparative Example 2, it is believed that these Examples have higher glass transition temperatures (Tg) and smaller mass loss rates than the corresponding Comparative Examples. It is believed that the coating films formed from the coating compositions obtained in Comparative Examples 1 and 3 to 10 exhibit the same anticorrosive properties as in Comparative Example 2.
[0108] [Table 1]
[0109] [Table 2]
[0110] [Table 3]
[0111] [Table 4] [Explanation of symbols]
[0112] 1: Test plate (for evaluating corrosion resistance) 2: Cut
Claims
1. A coating composition comprising an epoxy resin (A), a silicone resin (B), aluminum (C), and an amine-based curing agent (D), The weight average molecular weight of the silicone resin (B) is 15,000 or more, The coating composition has a VOC (volatile organic component) content of 354 to 700 g / L; The content of the solid content of the silicone resin (B) relative to the non-volatile content of the coating composition is 1 to 26 mass%; Paint composition.
2. A coating composition as described in claim 1, wherein the solid content of the epoxy resin (A) relative to the non-volatile content of the coating composition is 8 to 60 mass%.
3. A coating composition according to claim 1 or 2, wherein the ratio ((A):(B)) of the solid content of the epoxy resin (A) to the solid content of the silicone resin (B) is 1 to 50:
1.
4. The coating composition described in any one of claims 1 to 3, wherein the amine-based curing agent (D) is an amine adduct with an epoxy compound.
5. The coating composition according to any one of claims 1 to 4, further comprising a silane coupling agent.
6. The coating composition according to any one of claims 1 to 5, which is a heat-resistant coating composition.
7. A method for producing a substrate having a coating film, comprising the following steps [1] and [2]: [1] A step of coating a substrate with the coating composition according to any one of claims 1 to 6. [2] A step of drying the coating composition applied to the substrate to form a coating film.
Citation Information
Patent Citations
Anticorrosion coating for buried steel component as well as preparation method and application of anticorrosion coating
CN107513348A
High-temperature-resistant coating for transformer and preparation method of coating
CN107746653A
JP1972003709B1
Heat-resistant paint for part of engine and exhaust system
JP1986258871A
Heat-resistant paint composition
JP1988023975A
